(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
The focus on computer security has increased due to the ubiquitous use of Internet. Botnets are one of the biggest cyber threats. Botnet is a malware controlled by a Botmaster using Command and Control (C&C). Botnet is expanded with infecting fresh computers through social networking sites like facebook, twitter, etc. ZeuS is famous type of botnet for financial gain. It targets bank websites for stealing user’s credentials like password, credit card information,etc. In this paper, an application framework is designed for analysis and detection of ZeuS bot residing on host victim’s machine. The detection phase is based on analysis of bot’s infection stategy means in what way it affects the victims’s pc. All the related files are wiped out from the system in removal phase. The communication between command and control server and the victim machine is analysed in a virtual environment.